Constant Light Exerted Detrimental Cardiovascular Effects Through Sympathetic Hyperactivity in Normal and Heart Failure Rats - Jing, Jia-Ni; Wu, Zhao-Tang; Li, Miao-Ling; Wang, Yang-Kai; Tan, Xing; Wang, Wei-Zhong (Frontiers in Neuroscience, 2020)
It has been documented that constant light exposure exerts complicated cardiovascular effects. However, a mounting collection of conflicting results did not make it any easier for researchers and physicians to consider the role of light on cardiovascular function. This study was designed to investigate how constant light exposure (24-hour light/day) influences the cardiac function in normal and heart-failure (HF) rats. In normal rats, two groups of SD rats were accustomed in 12-hour light/ 12-hour dark (LD) or 24-hour light (constant light, CL) for 4 weeks. In HF rats which was induced by myocardial infarction (MI) was let recover in LD for 4 weeks. Interestingly, compared with rats in LD environment (ejection fraction, EF %: 93.64±2.02 in LD, 14.62±1.53 in HF-LD), constant light (2 weeks) weakened the cardiac function in normal and HF rats (EF%: 79.42±2.91 in CL, 11.50±1.08 in HF-CL). The levels of renal sympathetic nerve activity and c-fos expression in the rostral ventrolateral medulla (RVLM), a key region controlling sympathetic outflow, were significantly increased in normal and HF rats after contant light (RSNA, Max%: 8.64±0.48 in LD, 20.02±1.24 in CL, 20.10±1.16 in HF-LD, 26.82±1.69 in HF-CL).. In conclusion, it is suggested that constant light exposure exerts detrimental cardiovascular effects, which may be associated with the RVLM-related sympathetic hyperactivity.